A study on the reality of educational evaluation in the Algerian school from the teachers' point of view - Nacira, Lamouri (International Journal of Psychosocial Rehabilitation, 2022)
In the past few years, Algeria’s educational system has adopted a series of reforms, including theintroduction of the competency-based approach that has profoundly altered educational evaluation. This latter is an essential component of the curriculum that identifies and then remediates the learners' strengths and weaknesses, thus achieves the goals set out in the educational process.For this purpose, the study aimed to understand the reality of the educational evaluation process from the teachers’ point of view. A questionnaire was presented and distributed to a sample of 70 teachers in middle school, using quantitative and qualitative methods to analyze the study data with the calculation of the Q2 test.The study results revealed that the training of teachers and the school factors were not statistically significant in the educational evaluation process.